Health status, functioning and risk profiles for secondary health conditions in adolescents and young adults with spina bifida: a cross-sectional study at time of transition (Swiss Medical Weekly, 2024)
INTRODUCTION: The transition from paediatric to adult medical care is a critical period for adolescents with spina bifida, often marked by deteriorating health and functional status.OBJECTIVES: To describe the health status and functioning of individuals with spina bifida at the time of transition from paediatric to adult care and to identify risk profiles for potentially modifiable secondary health conditions (urinary tract infections, pressure injuries, respiratory problems and obesity).METHODS: Descriptive study of data (derived from medical records) from all adolescents and young adults with spina bifida aged 15–25 years who were referred to a single specialised spinal cord injury centre as part of the transition programme during the period from 1 September 2015 to 31 May 2022. Descriptive statistics were used to describe the study population and to analyse the frequency and co-occurrence of congenital and acquired secondary health conditions. The equality of proportions test was used to test the prevalence of secondary health conditions based on important personal and clinical characteristics.RESULTS: We included 43 adolescents with spina bifida with a mean age of 18.4 years (SD 2.5); in 63% of them the neurological level was lumbar, and around 50% of them were wheelchair-dependent. The median Spinal Cord Injury Measure (SCIM) III score was 72 (IQR 61–89). The mean number of secondary health conditions at time of transition was 8.8. The most prevalent secondary health conditions were lower urinary tract dysfunction, bowel dysfunction, sexual dysfunction and contractures. Respiratory problems were more prevalent in females and in individuals with lower SCIM III scores, whereas no differences were observed in the prevalence of other modifiable secondary health conditions. Clustering of secondary health conditions was mainly seen for urinary tract infection + pressure injury and for urinary tract infection + pressure injury + obesity.CONCLUSION: The prevalence of secondary health conditions among individuals with spina bifida at time of transition is alarmingly high and functional profiles underscore the need for supporting adolescents and young adults with daily medical issues. The study highlights the critical role of transition programmes and interdisciplinary follow-up care in preventing health problems and improving functioning and independence in everyday life.